Identity evolution of STEM teachers in Egyptian STEM schools in a time of transition: a case study - Mohamed El Nagdi; Gillian Roehrig (SpringerOpen, 2020)
Abstract Background The study was initiated as a response to the growing Science, Technology, Engineering, and Mathematics (STEM) experience in Egypt in terms of the growing number of schools, number of students admitted, and the effect of this experience on the overall education system in the country. Viewing teachers as the backbone of the STEM experience and teaching as a relational sociocultural practice (Biesta, G. & Stengel, B. (2016) AREA Handbook of research on teaching, 5th edition), this research explores the evolution of teachers' STEM identity during their professional journey in the Egyptian STEM education reform initiative. Aim The purpose of this study is to explore the dynamic dialogical interaction between the different factors impacting the development/evolution of the STEM teachers' identity. The study is guided by the following research questions: 1) How did Egyptian STEM teachers' identity evolve over the course of the STEM experience in model STEM schools in Egypt? 2) How did the political and structural characteristics of the STEM schools and teachers developing STEM identities interact and co-evolve? 3) What do Egyptian STEM teachers identify as being important characteristics of STEM teachers Methodology A multiple holistic case study design was used to explore the research questions within the bounded context of an established Egyptian STEM school. Methods Data for this study were drawn from (1) semi-structured interviews conducted with seven teachers from an Egyptian STEM school and (2) document analysis of Ministry of Education decrees and the published reports of Education Consortium for the Advancement of STEM in Egypt. Results Using inductive and deductive data analysis, teachers were found to have undergone a deep transformative change process from a traditional teacher into teachers with a progressive mindset and student-centered classroom practices. The teachers developed strong conceptualizations of the STEM education, stressed the importance of collaboration, critical thinking, and motivation for teachers seeking to work in a STEM setting, and considered themselves moving towards established STEM teachers' identity. Conclusion This study concluded that STEM teachers' identity can be viewed as a dialogical, dynamic, and evolving process that results from the interaction of personal and professional traits within new educational experiences exemplified by the new and different experiences in their STEM schools. Despite several challenges, such as limited resources and influence from the bureaucracy and norms of the traditional education system, the teachers still persist in their professional growth and desire to impact the larger context of the Egyptian education system.